Workplace stress in community pharmacies in England: associations with individual, organizational and job characteristics. (January 2014) - Jacobs, Sally; Hassell, Karen; Ashcroft, Darren; Johnson, Sheena; O'Connor, Elinor
Objectives: To describe the levels of workplace stress that community pharmacists perceive and to examine associations with individual, organizational and job characteristics. Methods: A cross-sectional mailed survey of 2000 randomly selected community pharmacists practising in England incorporating a validated organizational stress screening tool (ASSET). Results: Response rate was 48%. Community pharmacists reported significantly higher levels of stress than other health care workers for seven out of eight work-related stressors. Regression analyses demonstrated significant associations between a number of individual, organizational and job characteristics and stress. Long working days, being a pharmacy manager and working for large multiples were associated with higher reported levels of stress across a number of work-related stressors including work overload, control and the job itself. However, self-reported measures of workload (such as dispensing volume) were not associated with higher stress levels. Conclusions: The growth in corporate ownership of community pharmacies, which is associated with more stressful working environments, together with current economic pressures could have consequences not only for the future well-being of pharmacists but also for patient safety.